Shear bond strength of three luting cements to two ceramic materials - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
The aim of this study was to evaluate the shear bond strength of three different dual cure luting cements to two ceramic materials. Sixty cylindrical specimens (4mm in diameter) were prepared with Finesse Ceramco and Vita Omega 900. Specimens were randomly diveded into six groups of 10 specimen each. The luting cements (Panavia F; 3M ESPE Opal Luting Cement; Variolink H) were bonded to ceramic specimens using teflon tubes with an internal diameter of 2,97 nun and 2 mm in hight. Following thermocycling, the sepecimens were mounted in a spesific jig on the Universal Testing Machine and the luting cements debonded under a shear force at a crosshead speed of 0.5 mm/min. The bond strength was calculated in Mpa. The values of the shear bond strengths were analysed by using Two Way ANOVA, Kruskal-wallis of One Way ANOVA and Mann-Whitney U test. There were no statistically significant differences between the bond strength values of Finesse and Vita Omega 900 porcelains. Dual-cure cements (Panavia F and Variolink H) showed higher bond strength than light cure cement (3M ESPE Opal Luting cement).
Keywords: ceramic; luting cement; bonding; SURFACE TREATMENTS; COMPOSITE RESIN; PORCELAIN; AGENTS